2021
DOI: 10.3390/antibiotics10091119
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin to Guide Antibacterial Prescribing in Patients Hospitalised with COVID-19

Abstract: Antibacterial prescribing in patients presenting with COVID-19 remains discordant to rates of bacterial co-infection. Implementing diagnostic tests to exclude bacterial infection may aid reduction in antibacterial prescribing. (1) Method: A retrospective observational analysis was undertaken of all hospitalised patients with COVID-19 across a single-site NHS acute Trust (London, UK) from 1 December 2020 to 28 February 2021. Electronic patient records were used to identify patients, clinical data, and outcomes.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
1
13
1
Order By: Relevance
“…Hughes et al [ 26 ] highlighted a high prescription rate of antibiotics in patients with COVID-19 pneumonia, with special reference to antibiotics against Gram-negative microorganisms. Our antibiotic use data confirm their observation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hughes et al [ 26 ] highlighted a high prescription rate of antibiotics in patients with COVID-19 pneumonia, with special reference to antibiotics against Gram-negative microorganisms. Our antibiotic use data confirm their observation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in our COVID-19 wards, the most used antibiotic was piperacillin/tazobactam, a beta-lactam/beta-lactamase inhibitor combination which use is highly recommended in community bacterial pneumonitis needing admission in hospital, but also in UTI, abdominal infections, and infections caused by sensitive Gram-negative bacteria. Hughes also studied an approach based on the use of procalcitonin (PCT) to stratify people at risk of having a bacterial co-infection or superinfection within the first 72 h from admission in order to reduce the improper use of empiric antibiotics [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of COVID-19 patients have documented stopping antibiotics in patients with normal PCT without an increase in mortality [ 17 ]. Another study showed that normal PCT on admission correlates with shorter antimicrobial courses and early stopping of therapy as well as predicts a lower frequency of ICU admission [ 18 ]. The difference in our results and others could be for many reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiologically confirmed diagnosis of infection has been shown to represent 50–75% of infections on the ICU, and it is currently unknown which is the best way to approach the diagnosis of culture-negative suspected bacterial infections in the context of COVID-19 ARDS [ 34 ]. Biomarkers associated with the development of such infections could be useful tools at the bedside [ 35 ].…”
Section: Discussionmentioning
confidence: 99%